Acute resistance exercise using free weights on aortic wave reflection characteristics. (19th October 2016) - Tai, Yu Lun; Gerhart, Hayden; Mayo, Xián; Kingsley, J. Derek
Summary: Aortic wave reflection characteristics such as the augmentation index (AIx), wasted left ventricular pressure energy (Δ E w ) and aortic haemodynamics, such as aortic systolic blood pressure (ASBP), strongly predict cardiovascular events. The effects of acute resistance exercise (ARE) using free‐weight exercises on these characteristics are unknown. Therefore, we sought to determine the effects of acute free‐weight resistance exercise on aortic wave reflection characteristics and aortic haemodynamics in resistance‐trained individuals. Fifteen young, healthy resistance‐trained (9 ± 3 years) individuals performed two randomized sessions consisting of an acute bout of free‐weight resistance exercise (ARE) or a quiet control (CON). The ARE consisted of three sets of 10 repetitions at 75% one repetition maximum for squat, bench press and deadlift. In CON, the participants rested in the supine position for 30 min. Measurements were made at baseline before sessions and 10 min after sessions. A two‐way ANOVA was used to compare the effects of condition across time. There were no significant interactions for aortic or brachial blood pressures. Compared to rest, there were significant increases in augmentation pressure (rest: 5·7 ± 3·0 mmHg; recovery: 10·4 ± 5·7 mmHg, P  = 0·002), AIx (rest: 116·8 ± 4·2%; recovery: 123·2 ± 8·4%, P  = 0·002), AIx normalized at 75 bpm (rest: 5·2 ± 7·6%; recovery: 27·3 ± 13·2%, P <0·0001), Δ E w (rest: 1215 ± 674 dynes s cm −2 ; recovery: 2096 ± 1182 dynes s cm −2, P  = 0·008), and there was a significant decrease in transit time of the reflected wave (rest: 150·7 ± 5·8 ms; recovery 145·5 ± 5·6 ms, P <0·001) during recovery from ARE compared to CON. These data suggest that ARE using free‐weight exercises may have no effect on aortic and brachial blood pressure but may significantly alter aortic wave reflection characteristics.